Working with Female Participants for Field Work Photographic Practice in Saudi Arabia. A Case Study (Global Journal of Human-Social Science, 2018)
My research project documented in this article explores the visual representation of ten Saudi women living in Saudi Arabia. Photography is used as a medium and a critical tool to examine and reframe the representations of Saudi women in a collaborative process. The aims of the project are to understand the place of photography in Saudi women's experience and selfperception; to analyse their response to its creative potential as a tool of self-presentation; to reveal the full potential of creative collaborative photography in research and to explore the complexity and diversity of Saudi women's identities. My research will nuance and contradict the stereotypes about Saudi women depicted as either victims of Islam or the state, covered in black veils, or wealthy women enjoying the luxuries of oil wealth and will illustrate the diversity and complexity of Saudi women who range from extreme religious fundamentalists to young, modern, liberal feminists. Through the women involved, the project introduces a complex and dynamic picture of Saudi society today.
Keywords: fieldwork; saudi arabia; saudi women; stereotypes; photography and photographic portraiture; photo-elicitation